2006
DOI: 10.1530/eje.1.02110
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal incidentaloma – follow-up results from a Swedish prospective study

Abstract: Objectives: To examine the risk of developing adrenal carcinomas and clinically overt hypersecreting tumours during short-term follow-up in patients with adrenal incidentalomas. Design: 229 (98 males and 131 females) patients with adrenal incidentalomas were investigated in a prospective follow-up study (median time 25 months; range 3-108 months). The patients were registered between January 1996 and July 2001 and followed until December 2004. Twenty-seven Swedish hospitals contributed with follow-up results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
16

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 22 publications
7
71
0
16
Order By: Relevance
“…Control tests (both imaging and laboratory) should be planned individually taking into consideration such factors as tumour size, image and growth dynamics, clinical manifestations, hormonal tests results, as well as concomitant diseases, including neoplasms [57][58][59][60][61][62][63]. …”
Section: How To Monitor Adrenal Tumours Not Qualified For Surgicmentioning
confidence: 99%
See 3 more Smart Citations
“…Control tests (both imaging and laboratory) should be planned individually taking into consideration such factors as tumour size, image and growth dynamics, clinical manifestations, hormonal tests results, as well as concomitant diseases, including neoplasms [57][58][59][60][61][62][63]. …”
Section: How To Monitor Adrenal Tumours Not Qualified For Surgicmentioning
confidence: 99%
“…Tumours larger than 3 cm are more frequently hormonally active than smaller lesions [61]. The risk of an excessive hormonal secretion by an adrenal tumour reaches a plateau after 3-5 years [58]; hence, further control is not necessary. -Patients with suspected subclinical hypercortisolism require control tests assessing adrenocortical axis function as well as a precise control of the diseases associated with an excess of glucocorticoids (obesity, diabetes, hypertension, osteoporosis).…”
Section: Hormonal Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10,11] However, diverse opinions about approach to smaller mass lesions are available in the literature. Bulow et al [12] followed up 229 patients with adrenal masses for 30 months, and observed development of hormonal activity only in 3% of these patients. On the other hand, Liebe et al [13] followed up 64 patients for 3 years, and reported development of endocrinological disorders in 28% of these patients, and higher risk in patients with adrenal masses greater than 3 cm in diameter.…”
Section: Discussionmentioning
confidence: 99%